Control of Saccharomyces cerevisiae pre-tRNA processing by environmental conditions - Foretek, Dominika (RNA, 2016)
tRNA is essential for translation and decoding of the proteome. The yeast proteome responds to stress and tRNA biosynthesis contributes in this response by repression of tRNA transcription and alterations of tRNA modification. Here we report that the stress response also involves processing of pre-tRNA 3′ termini. By a combination of Northern analyses and RNA sequencing, we show that upon shift to elevated temperatures and/or to glycerol-containing medium, aberrant pre-tRNAs accumulate in yeast cells. For pre-tRNA(UAU)(Ile) and pre-tRNA(UUU)(Lys) these aberrant forms are unprocessed at the 5′ ends, but they possess extended 3′ termini. Sequencing analyses showed that partial 3′ processing precedes 5′ processing for pre-tRNA(UAU)(Ile). An aberrant pre-tRNA(Tyr) that accumulates also possesses extended 3′ termini, but it is processed at the 5′ terminus. Similar forms of these aberrant pre-tRNAs are detected in the rex1Δ strain that is defective in 3′ exonucleolytic trimming of pre-tRNAs but are absent in the lhp1Δ mutant lacking 3′ end protection. We further show direct correlation between the inhibition of 3′ end processing rate and the stringency of growth conditions. Moreover, under stress conditions Rex1 nuclease seems to be limiting for 3′ end processing, by decreased availability linked to increased protection by Lhp1. Thus, our data document complex 3′ processing that is inhibited by stress in a tRNA-type and condition-specific manner. This stress-responsive tRNA 3′ end maturation process presumably contributes to fine-tune the levels of functional tRNA in budding yeast in response to environmental conditions.